Global and national assessment of the incidence of asthma in children and adolescents from major sources of ambient NO2. (8th March 2021) - Chowdhury, Sourangsu; Haines, Andy; Klingmüller, Klaus; Kumar, Vinod; Pozzer, Andrea; Venkataraman, Chandra; Witt, Christian; Lelieveld, Jos
Abstract: Pediatric asthma incidence has been associated with exposure to nitrogen dioxide (NO2 ) in ambient air. NO2 is predominantly emitted through fossil fuel use in land transportation, power generation and the burning of solid biofuels in households. We simulated NO2 with a global atmospheric chemistry model, combined with a land use regression model, to estimate NO2 exposure in all countries worldwide. The global asthma incidence among children and adolescents attributable to NO2 was estimated by deriving an exposure-response function from a meta-analysis which included epidemiological studies from multiple countries, baseline incidence rates from the Global Burden of Disease and gridded population data. The sectoral contribution to pediatric asthma from NO2 exposure (NO2 -related asthma incidence: NINC) was estimated for different source categories to provide guidance to mitigation policies. We estimate 3.52 (2.1–6.0) million NINC per year globally, being about 14% of the total asthma incidence cases among children and adolescents. We find that emissions from land transportation are the leading contributor to NINC globally (∼44%), followed by the domestic burning of solid fuels (∼10.3%) and power generation from fossil fuels (∼8.7%). Biogenic emissions which are not anthropogenically induced may contribute ∼14% to the total NINC. Our results show large regional differences in source contributions, as the domestic burning of solid fuels is a main contributor to NINC in India and Nepal (∼25%), while emissions from shipping are the leading source in Scandinavian countries (∼40%), for example. While only 5% of all children and adolescents live in areas where NO2 exceeds the WHO annual guideline of 21.25 ppb (40 μ g m −3 ) for NO2, about 90% of the NINC is found in regions that meet the WHO guideline, related to the uneven distribution of children and adolescents in the population. This suggests the need for stricter policies to reduce NO2 exposure, and revisiting the current WHO guideline to reduce the health risks of children and adolescents.